Irisin protects heart against ischemia-reperfusion injury through a SOD2-dependent mitochondria mechanism - Wang, Zhen (J Cardiovasc Pharmacol, 2018)
Irisin, a muscle-origin protein derived from the extracellular domain of the fibronectin domain-containing 5 protein (FNDC5), has been shown to modulate mitochondria welfare through paracrine action. Here we test the hypothesis that irisin contributes to cardioprotection after myocardial infarction by preserving mitochondrial function in cardiomyocytes. Animal model studies show that intravenous administration of exogenous irisin produces dose-dependent protection against ischemia/reperfusion (I/R)-induced injury to the heart as reflected by the improvement of left-ventricular ejection fraction and the reduction in serum level of cTnI (n=15, P<0.05). I/R-induced apoptosis of cardiomyocytes is reduced after irisin treatment. The irisin-mediated protection has, at least in part, an effect on mitochondrial function because administration of irisin increases irisin staining in the mitochondria of the infarct area. Irisin also reduces I/R-induced oxidative stress as determined by mitochondrial membrane potential evaluation and superoxide FLASH event recording (n=4, P<0.05). The interaction between irisin and SOD2 plays a key role in the protective process because irisin treatment increases SOD activity (n=10, P<0.05) and restores the mitochondria-localization of SOD2 in cardiomyocytes (n=5, P<0.05). These results demonstrate that irisin plays a protective role against I/R injury to the heart. Targeting the action of irisin in mitochondria presents a novel therapeutic intervention for myocardial infarction.